2018
DOI: 10.1016/j.jchf.2018.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Baseline Physical Activity Level on Exercise Training Response and Clinical Outcomes in Heart Failure

Abstract: OBJECTIVES This study sought to evaluate the influence of baseline physical activity (PA) on responses to aerobic exercise training and clinical events in outpatients with chronic systolic heart failure (HF) from the multicenter HF-ACTION (Exercise Training Program to Improve Clinical Outcomes in Individuals With Congestive Heart Failure) trial. BACKGROUND The influence of baseline PA on exercise capacity, responses to exercise training and clinical outcomes in patients with chronic HF is unclear. METHODS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 35 publications
(34 reference statements)
2
17
0
3
Order By: Relevance
“…Our findings support the universal positive impact of exercise therapy for individuals with knee OA, regardless of pre‐participation PA levels. Similarly, a recent report of patients with systolic heart failure found comparable benefits of exercise training on exercise capacity, mortality, and hospitalization across all baseline self‐reported PA tertiles . These observations reinforce that exercise training should be an integral part of therapeutic strategies for all older adults with chronic health conditions, even in those who are already physically active prior to participation.…”
Section: Discussionsupporting
confidence: 60%
“…Our findings support the universal positive impact of exercise therapy for individuals with knee OA, regardless of pre‐participation PA levels. Similarly, a recent report of patients with systolic heart failure found comparable benefits of exercise training on exercise capacity, mortality, and hospitalization across all baseline self‐reported PA tertiles . These observations reinforce that exercise training should be an integral part of therapeutic strategies for all older adults with chronic health conditions, even in those who are already physically active prior to participation.…”
Section: Discussionsupporting
confidence: 60%
“…(1) Exercise alleviates heart failure. An action trial with more than 3000 participants found that aerobic exercise causes a significant decrease in heart failure hospitalizations as well as decreased cardiovascular events 21 . (2) Exercise protects heart against MI, inhibiting the release of cardiac proinflammatory factors, which prevents pathologic changes 22 .…”
Section: Exercise Reduces the Risk For Cvdsmentioning
confidence: 99%
“…4,16,45,46 P h y s i c a l a c t i v i t y a n d c a r d i a c rehabilitation. 4,16,[46][47][48][49][50][51]…”
Section: Routine Consumption Of Dietar Y Supplements Including Vitamins Is Notunclassified